2010
DOI: 10.21236/ada528597
|View full text |Cite
|
Sign up to set email alerts
|

Performance Effects of Measurement and Analysis: Perspectives from CMMI High Maturity Organizations and Appraisers

Abstract: ixii | CMU/SEI-2010-TR-022iii | CMU/SEI-2010-TR-022 List of Tables Table 1: Relationships between individual items about the of use of healthy process performance model ingredients and overall value 49 Table 2: Relationships between individual items about the of use of statistical methods for process performance modeling and overall value 52 Table 3: 2009 -Relationships between the use of automated method to support measurement related activities and overall value attributed to process performance modeling 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Most recently an ISO standard [3] for how to diagnose -or assess as it is called -was published along with a maturity model. Studies have shown [4][5][6] that increasing your maturity as an IT or Software developing company bring about real benefits such as higher quality of your products, less rework, and faster development of new products.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently an ISO standard [3] for how to diagnose -or assess as it is called -was published along with a maturity model. Studies have shown [4][5][6] that increasing your maturity as an IT or Software developing company bring about real benefits such as higher quality of your products, less rework, and faster development of new products.…”
Section: Introductionmentioning
confidence: 99%